Effects of a neo-functional psychotherapeutic approach on post-traumatic stress disorder following spontaneous coronary artery dissection: a case report - Emilia Solinas; Filippo Luca Gurgoglione; Andrea Denegri; Giorgio Benatti; Rossella Giacalone; Manjola Noni; Giulia Magnani; Luigi Vignali; Giampaolo Niccoli; Caterina Viaro; Enrica Pedrelli; Rita Pinetti; et al. (Frontiers in Cardiovascular Medicine, 2026)
Background Post-traumatic stress disorder (PTSD) is increasingly recognized after acute coronary syndromes, including spontaneous coronary artery dissection (SCAD), a condition predominantly affecting women. PTSD symptoms may negatively influence autonomic regulation, adherence to therapy, and cardiovascular outcomes. Evidence regarding structured psychotherapeutic interventions targeting SCAD-related PTSD is limited. Case presentation A 58-year-old woman was admitted with non–ST-elevation myocardial infarction due to SCAD involving the first obtuse marginal branch of the circumflex artery, managed conservatively. The event occurred one day after the sudden death of her son. Psychological evaluation revealed severe PTSD (Impact of Event Scale-Revised score: 57), characterized by hyperarousal, intrusive memories, avoidance, and sleep disturbance. The patient underwent a 12-month Neo-Functional Psychotherapeutic Approach integrated within cardiologic follow-up. The intervention included grounding techniques, diaphragmatic breathing, emotional processing, and cognitive restructuring. Results At 6 months, psychometric reassessment showed a reduction in stress indices. Holter-based heart rate variability (HRV) demonstrated preserved vagal-related activity indices (SDNN 120–130 ms; RMSSD 38–40 ms). Clinically, intrusive symptoms and somatic hyperarousal progressively decreased, accompanied by improvement in social and daily functioning. Conclusion This case suggests that integration of a structured body-oriented psychotherapeutic intervention within cardiologic care is feasible and may be associated with psychological improvement and favorable autonomic modulation in PTSD following SCAD. Larger prospective studies are warranted these preliminary observations.